Internal corporate social responsibility practices and employees’ job satisfaction in a Malaysian banking company - Chan, Tak Jie; Nurul Ain Mohd Hasan (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to examine the relationship between internal corporate social responsibility (CSR) practices and job satisfaction of employees in a Malaysian banking company. The study utilised Carroll’s revised pyramid of global CSR and performance model with the selected CSR dimensions developed by Mohd Hasan (2013), consisting of the best global and local CSR practices. Multistage sampling, simple random sampling and convenient sampling was used. This study employed a quantitative (survey) method, wherein questionnaires were distributed to 342 bank staff (managerial and non-managerial), but only 174 valid responses were received. The data were analysed using Pearson-Product Moment Correlation test and Multiple Regression test through the Statistical Package for the Social Sciences (SPSS) version 22.0. The findings of multiple regression analysis revealed that human rights, labour rights and compliance with certified international standards pertaining to ethical and legal aspects of internal CSR were significant predictors of job satisfaction in the current context. Conclusion, limitations, implications of the findings, and suggestions for future study are also discussed.